2022
DOI: 10.1155/2022/2180795
|View full text |Cite
|
Sign up to set email alerts
|

Treating Acute Severe Eosinophilic Asthma with IL-5 Inhibitors in ICU

Abstract: Introduction. About 10% of the 300 million people worldwide who suffer from asthma have a severe disease that is uncontrolled despite treatment with inhaled corticosteroids and long-acting beta agonists. The eosinophilic inflammation pathway in the respiratory tract and blood is involved and interleukin-5 (IL-5) has recently been identified as a major promotor of this pathway. The anti-IL-5 antibodies reduce the incidence of exacerbation and allowed steroid sparing in severe asthma patients but only two case r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…[1] About 10% of the 300 million people worldwide suffer from asthma. [5] This case report demonstrated the efficacy of bendralizumab treatment in a patient with uncontrolled severe eosinophilic asthma refractory to omalizumab treatment and another study conducted by Adel H. Mansur et al reported the efficacy of bendralizumab treatment in a patient with severe eosinophilic asthma and chronic rhinosinusitis with nasal polyps refractory to mepolizumab treatment. [3] In the present study, treatment of uncontrolled severe eosinophilic asthma with bendralizumab appears to be feasible, rapid and safe.…”
Section: Discussionmentioning
confidence: 50%
“…[1] About 10% of the 300 million people worldwide suffer from asthma. [5] This case report demonstrated the efficacy of bendralizumab treatment in a patient with uncontrolled severe eosinophilic asthma refractory to omalizumab treatment and another study conducted by Adel H. Mansur et al reported the efficacy of bendralizumab treatment in a patient with severe eosinophilic asthma and chronic rhinosinusitis with nasal polyps refractory to mepolizumab treatment. [3] In the present study, treatment of uncontrolled severe eosinophilic asthma with bendralizumab appears to be feasible, rapid and safe.…”
Section: Discussionmentioning
confidence: 50%
“…Individuals with mild to moderate asthma with associated diseases whose pathogenesis consists of eosinophilia, such as rhinosinusitis with nasal polyps, allergic rhinitis, and allergic dermatitis, should be considered as possible candidates for monoclonal antibodies to decreased morbidity and mortality. One case report describing a 31-year-old male with allergic dermatitis and mild asthma controlled on demand with inhaled salbutamol was admitted for asthma exacerbation [ 15 ]. The hospital course was complicated by respiratory distress, despite methylprednisolone (2 mg/kg) and salbutamol nebulizers, with eventual orotracheal intubation and venovenous extracorporeal membrane oxygenation (VV-ECMO) placement.…”
Section: Discussionmentioning
confidence: 99%
“…One patient, with severe EA placed on VV-ECMO, was treated with IL-5 monoclonal antibody. And another patient with severe EA on IMV received mepolizumab with successful clinical improvement [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that, omalizumab—a monoclonal antibody which targets immunoglobulin E—represents the first available humanized monoclonal anti-IgE for use in pediatric severe allergic asthma (approved for use in children ≥ 6 years of age), with an established efficacy and safety profile ( Licari et al, 2019 ). Mepolizumab—a monoclonal antibody against interleukin-5— is an effective and well-tolerated treatment that reduces the risk of asthma exacerbations in patients with severe eosinophilic asthma ( Pavord et al, 2012 ) and also be useful in an emergency to treat steroid-refractory eosinophilic acute severe asthma ( Barbarot et al, 2022 ). Phenotype-directed therapy with mepolizumab in urban children (aged 6–17 years) with exacerbation-prone eosinophilic asthma reduced the number of exacerbations ( Jackson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%